Empowerment of women representatives in panchayati raj - Singh, Surat (2004)
This article seeks to present the findings of an empirical study of the elected women representatives of the Panchayati Raj Institutions of Haryana for exploring the extent of their empowerment as a result of the implementation of the 73rd Amendment to the Indian Constitution which made provision for the reservation of one-third share for women in these institutions. It also aims at making some suggestions for making the participation of women effective in these institutions of decentralized rural governance. - Reproduced.
Keywords: Panchayat - India - Haryana; Women in politics - India - Haryana; Women in politics